Supplier Selection Decision Support System in Coffee Shops During the Covid- 19 Pandemic (Case Study: Lucky's Koffiee) - Rezky Puteri Sariaji; Asep Juarna (Dinasti Publisher, 2022)
Enjoying a cup of coffee is one of the hobbies of most people in Indonesia in various circles, both young and old. However, since the Covid-19 outbreak, the government has asked the public to reduce activities outside the home. Lucky's Koffiee is feeling the impact of this epidemic. Experiencing a decrease in revenue and the amount of raw material remaining is an important concern for management. Using Rank Order Centroid (ROC) for weighting criteria and a decision support system using the Simple Additive Weighting (SAW) method as consideration for selecting suppliers of raw materials that are in accordance with the conditions of the Covid- 19 pandemic by using the criteria of price, quality, service, and timeliness as consideration variables.